2006
DOI: 10.1111/j.1462-2920.2006.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical prey recognition by planktonic protozoa

Abstract: Planktonic flagellates and ciliates are the major consumers of phytoplankton and bacterioplankton in aquatic environments, playing a pivotal role in carbon cycling and nutrient regeneration. Despite certain unicellular predators using chemosensory responses to locate and select their prey, the biochemical mechanisms behind prey reception and selection have not been elucidated. Here we identify a Ca(2+)-dependent, mannose-binding lectin on the marine dinoflagellate Oxyrrhis marina, which is used as a feeding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 37 publications
2
95
0
Order By: Relevance
“…Prior investigations of endocytosis in marine heterotrophic protists revealed that protein kinases (Hartz et al, 2008) and lectins (Wootton et al, 2007) can be directly linked to phagocytosis. Genes that clustered into category D in Alex2 included those for lectins (C-type and Ricin-B-type), which were significantly enriched in the expression analysis after 48 and 96 h ( Figure 5).…”
Section: Endocytotic Processes and Cell Recognition Featuresmentioning
confidence: 99%
“…Prior investigations of endocytosis in marine heterotrophic protists revealed that protein kinases (Hartz et al, 2008) and lectins (Wootton et al, 2007) can be directly linked to phagocytosis. Genes that clustered into category D in Alex2 included those for lectins (C-type and Ricin-B-type), which were significantly enriched in the expression analysis after 48 and 96 h ( Figure 5).…”
Section: Endocytotic Processes and Cell Recognition Featuresmentioning
confidence: 99%
“…Some 16 years ago it was proposed that certain protozoa might use 'contact chemoreceptors' to discern the profitability of different prey items on the basis of their cell-surface biochemical composition (28). However, exploration of molecular-level signalling and recognition processes between predatory and prey cells has only been pursued more recently (23,26,27,32). Of significance are the recent findings of Wootton et al (32) who identify a mannose-specific feeding receptor on the phagotrophic protozoan Oxyrrhis marina -a marine species in which selective feeding is well-documented (7,10,16,29).…”
mentioning
confidence: 99%
“…However, exploration of molecular-level signalling and recognition processes between predatory and prey cells has only been pursued more recently (23,26,27,32). Of significance are the recent findings of Wootton et al (32) who identify a mannose-specific feeding receptor on the phagotrophic protozoan Oxyrrhis marina -a marine species in which selective feeding is well-documented (7,10,16,29). Wootton and colleagues demonstrate that ingestion of the microalga Isochrysis galbana by O. marina can be inhibited by saturating receptor binding domains with mannose-BSA (32).…”
mentioning
confidence: 99%
See 2 more Smart Citations